Penurunan Nyeri Kaki Restless Leg Sindrome Pada Pasien Gagal Ginjal Kronik Melalui Intradialisis Range Of Motion Exercise Pasif - Putri Naila Fadlilatul Husna; Taufan Arif; Maria Diah Ciptaningtyas; Supono (Jurnal Keperawatan Muhammadiyah, 2023)
Introduction: Ureal buildup and inactivity can lead to complications of restless leg syndrome. The thing that is deeply felt in these complications is leg pain. The incidence of leg pain in RLS is 21.5–40% on a mild to moderate scale. RLS leg pain, if left continuously, can interfere with the patient's daily life and even affect the quality of life of patients with chronic kidney failure. The purpose of this study was to determine the effect of passive intradialysis range of motion exercise on the lower extremities on leg pain in patients with chronic renal failure.Method: The research design is "quasi-experimental" with a "pretest-posttest control group design" approach. The sampling method used was purposive sampling with 32 respondents divided into two groups. Determination of respondents based on inclusion criteria for CRF patients undergoing hemodialysis with leg pain (RLS) on a mild, moderate, or severe scale. The independent variable is intradialysis, passive range of motion exercise in the lower extremities, and the dependent is leg pain. The data analysis test uses univariate analysis to determine the characteristics of the respondents. Bivariate analysis used a pairend t-test and an independent t-test to determine the differences between the two groups.Results: Paired t-test on the pre-post control group was 0.083, with an increase in mean value of 0.19. While the pre-post treatment group was 0.000 with a decrease in the mean value of 2.19. Independent test t-test in the pre-test control and treatment groups was 0.230 and the post-test control and treatment group was 0.000.Discussion: Giving passive intradialysis range of motion exercises to the lower extremities affects the reduction in pain scale caused by the occurrence of vasodilation of blood vessels.